The use of religion by populist parties: the case of Italy and its broader implications - Caiani, Manuela; Carvalho, Tiago (Religion, state & society, 2021)
The rise of populist parties in Europe and the increasing salience of religion in political discourse are two relevant, sometimes discussed as interrelated, phenomena of recent decades. While most analysis focuses on right-wing populism, this does not exhaust all possible relationships. This study addresses the role of religion in populist parties by focusing on the Italian case and adopting a comparative cross organisational perspective shedding light on how left-wing and right-wing populists use religion for different purposes. Drawing on interview data with party representatives and analysis of organisational documents and speeches, we explore the presence and the uses of religious appeals in the two populist Italian parties in recent years. We show that their use of religion varies on three dimensions: i) hierarchy of identifications, ii) salience, and iii) frame. The League represents 'cultural populism': religion is used as an 'identity marker' that is highly salient and an instrument for framing specific topics. Conversely, the Five Star Movement exemplifies 'political/economic populism', in which religion as an identifier is present but less salient and used to frame citizenship in juridical/legalist terms. These different usages of religion lead to different definitions of the 'people' and therefore in-group constituencies.